Adjuvanted trivalent influenza vaccine versus quadrivalent inactivated influenza vaccine in Hutterite Children: A randomized clinical trial. Issue 47 (16th November 2021) - Loeb, Mark; Russell, Margaret L; Kelly-Stradiotto, Caralyn; Fuller, Nola; Fonseca, Kevin; Earn, David J.D.; Chokani, Khami; Babiuk, Lorne; Neupane, Binod; Singh, Pardeep; Pullenayegum, Eleanor
Highlights: One way to help achieve community protection against influenza is to vaccinate children. The best choice of influenza vaccine to achieve both direct and indirect protection is uncertain. Vaccinating children with aTIV compared to QIV results in similar community RT-PCR confirmed influenza illness. aTIV can lead to significant protection against influenza A in children. Abstract: Background: Children play an important role in the transmission of influenza. The best choice of vaccine to achieve both direct and indirect protection is uncertain. The objective of the study was to test whether vaccinating children with MF59 adjuvanted trivalent influenza vaccine (aTIV) can reduce influenza in children and their extended households compared to inactivated quadrivalent vaccine (QIV). Methods: We conducted a cluster randomized trial in 42 Hutterite colonies in Alberta and Saskatchewan. Colonies were randomized such that children were assigned in a blinded manner to receive aTIV (0.25 ml of pediatric aTIV for ages 6 months to < 36 months or 0.5 ml for ages ≥ 36 months to 6 years) or 0.5 ml of QIV. Participants included 424 children aged 6 months to 6 years who received the study vaccine and 1246 family cluster members who did not receive the study vaccine. The primary outcome was confirmed influenza A and B infection using a real-time reverse transcriptase polymerase chain reaction (RT-PCR) assay. An intent to treat analysis was used. Data were collected from January 2017 to June 2019. Results: The mean percentage of children who received study vaccine was 62% for aTIV colonies and 74% for QIV colonies. There were 66 (3.4%) with RT-PCR confirmed influenza A and B in the aTIV colonies (children and family clusters) versus 93 (4.4%) in the QIV colonies, hazard ratio (HR) 0.78 (95 %CI 0.36–1.71). Of these, 48 (2.5%) in the aTIV colonies and 76 (3.6%) in the QIV colonies had influenza A, HR 0.69, (95 %CI 0.29–1.66) while 18 (0.9%) and 17 (0.8%) in the aTIV versus QIV colonies respectively had influenza B, HR 1.22, (95 %CI 0.20–7.41). In children who received study vaccine, there were 5 Influenza A infections in the aTIV colonies (1.1%) compared to 30 (5.8%) in the QIV colonies, relative efficacy of 80%, HR 0.20, (95 %CI 0.06–0.66). Adverse events were significantly more common among children who received aTIV. No serious vaccine adverse events were reported. Conclusion: Vaccinating children with aTIV compared to QIV resulted in similar community RT-PCR confirmed influenza illness and led to significant protection against influenza A in children.